Beyond IQ: the role of emotional intelligence and spiritual intelligence in daily life - Abdul Rahman, Zanariah; Mat Din, Syaidatul Zarina; Othman, Akmal Aini (Universiti Teknologi MARA, Johor, 2025)
In an era defined by rapid technological advancement and social change, the ability to understand and manage emotions while finding meaning and purpose in life has become increasingly important. Two concepts that address these needs are Emotional Intelligence (EI) and Spiritual Intelligence (SI). Emotional Intelligence refers to the capacity to recognize, Spiritual Intelligence, on the other hand, involves the ability to apply spiritual values, meaning, and purpose to enhance daily functioning and relationships (Zohar & Marshall, 2000). Both forms of intelligence extend beyond cognitive or analytical skills, emphasizing the holistic nature of human development. In everyday life, EI and SI contribute to personal well-being, social relationships, workplace effectiveness, and overall life satisfaction.